2022
DOI: 10.1039/d2nj04373d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antiproliferative activity of 1H-1,2,3-triazole-4H-chromene-d-glucose hybrid compounds with dual inhibitory activity against EGFR/VEGFR-2 and molecular docking studies

Abstract: A series of 1H-1,2,3-triazole−4H-chromene−D-glucose hybrid compound 7a-o were synthesized by using click chemistry of 2-amino-7-propargyloxy-4H-chromene-3-carbonitriles 5a-o and peracetylated D-glucopyaranosyl azide. CuNPs@Montmorillonite K10 was used as catalyst in the presence of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Up to now, the CuAAC reaction has been extensively applied in various scientific fields, including materials, medicine, biology, , and catalysis . One prominent application is utilizing 1,2,3-triazole as a linker group to connect two functional segments.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, the CuAAC reaction has been extensively applied in various scientific fields, including materials, medicine, biology, , and catalysis . One prominent application is utilizing 1,2,3-triazole as a linker group to connect two functional segments.…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] The coumarin molecules are familiar and notorious moities with several applications, and vital action is occurring in arrears to concession of shape and physicochemical properties of the 2-benzopyrone entity. [11][12][13][14] However, coumarin and its derivatives were found to have a wide range of biological and pharmaceutical activities and have been used as good activity agents over decades for the cure of cancer and HIV, [15] coagulant, [16] oxidant [17] and inflammatory [18] and also used as the fascinating aspects to control or to heal of asthma and arthritis. [19] The synthesized derivatives of coumarin and Dgalactose moieties reports of Toan and coauthors showed worthy of action against EGFRÀ L858R and EGFRÀ T790 M tyrosine kinase.…”
Section: Introductionmentioning
confidence: 99%
“…[20] Mostly, the more active epidermal growth factor receptor (EGFR) can play a vital role in the growth and development of certain belligerent types of breast cancer. [12,13] Indeed, coumarin derivatives are found as essential drug agents for treating metabolic diseases. Furthermore, 4-hydroxycoumarin was used to reduce the reverse transcriptase activity of ACH-2-lymphocyte affected by the HIV [21] and the acylation of hydroxy groups at C-7&C-8 positions of 7,8-dihydroxycoumarin and C-7 position of the 7-hydroxycoumarin skeleton were elucidated the changing of G-protein-coupled receptor activators into inhibitors.…”
Section: Introductionmentioning
confidence: 99%